2021
DOI: 10.1097/qco.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in Clostridioides difficile infection epidemiology, diagnosis and treatment in children

Abstract: Purpose of review The US Centers for Disease Control and Prevention (CDC) classified Clostridioides difficile as an ‘urgent’ public health threat that requires ‘urgent and aggressive action’. This call to action has led to new discoveries that have advanced C. difficile infection (CDI) epidemiology, diagnosis and treatment, albeit predominantly in adults. In 2017, the Infectious Diseases Society of America and Society for Healthcare Epidemiology of America published clinical practice guidelines for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…As such methods rely on the amplification of specific DNA targets, they often have improved sensitivity compared to EIA tests. They however do not determine active toxin production or viability and, as such, are not appropriate in isolation for differentiating C. difficile infection from colonization [40]. It has also been suggested that the improved sensitivity of one-step molecular assay workflows may contribute to overdiagnosis of CDI in paediatric patients, subsequently leading to unnecessary antibiotic use [41].…”
Section: Diagnosismentioning
confidence: 99%
“…As such methods rely on the amplification of specific DNA targets, they often have improved sensitivity compared to EIA tests. They however do not determine active toxin production or viability and, as such, are not appropriate in isolation for differentiating C. difficile infection from colonization [40]. It has also been suggested that the improved sensitivity of one-step molecular assay workflows may contribute to overdiagnosis of CDI in paediatric patients, subsequently leading to unnecessary antibiotic use [41].…”
Section: Diagnosismentioning
confidence: 99%
“…Malignancy and multiple antibiotic treatments were identified as risk factors for severe CDI in a study of 82 patients [53,54].…”
Section: The Treatment Of Severe Clostridioides Difficile Infection I...mentioning
confidence: 99%
“…In addition, young children are often colonized by toxigenic strains while remaining asymptomatic (Collignon et al, 1993;Jangi and Lamont, 2010;Adlerberth et al, 2014). Therefore, children have long been considered to be at low risk for symptomatic CDI but the epidemiology of CDI in children has changed over the past decade (Kociolek et al, 2021). Similar to adult infections, severe cases, hypervirulent strains, more community-onset infections without previous antibiotic exposure, and outbreaks have been observed in pediatric populations (Noor and Krilov, 2018;Kociolek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%